Improving Reading Skills Through the SAS Method Based on Interactive Website Media - Sari, Endah Meilani; Wiarsih, Asih (CV. Tripe Konsultan, 2025)
Early reading skills play a crucial role in determining students' success in advanced reading. Therefore, teacher attention and intervention are essential in developing early reading skills. Early reading is seen as the primary foundation for subsequent learning, which must be built solidly and managed effectively. This study aims to improve reading skills in elementary school students. One approach offered is the application of the Synthetic Analytical Structure Method (SAS) combined with the use of website-based interactive media. This method is expected to significantly improve students' early reading skills. The study used a Classroom Action Research (CAR) design, implemented in two cycles, each encompassing four stages: planning, implementation, observation, and reflection. Research data were obtained through observation, interviews, assessment, and documentation techniques. The research results show that the use of the interactive web-based SAS method empirically improves students' reading skills in the early stages. This is demonstrated by the increase in completion rates from the pre-cycle (45%) to the second cycle (88%). This not only improved reading technique (pronounced letters and words), but also increased comprehension and desire to learn.